PENGARUH EFEKTIVITAS PEMIMPIN PADA LINGKUNGAN KERJA DAN DAMPAKNYA TERHADAP MOTIVASI PEGAWAI UNIVERSITAS ALKHAIRAAT PALU - Huzaemah, Huzaemah (Katalogis, 2015)
The objectives of this research is to know and analyze the efects of leadership effectivity at work environment and its impact on personnel motivation simultaneously and partially. This study involves 141 personnel at Alkhairaat University that have been determined using purposive sampling metod. Analysis method used in this research is SEM-PLS Work 3.0. the results show that leadership effectivity performs positive and significant effect on physical, non-physical work environment and job motivation. However, physical work environment does not perform an effect on job motivation of personnel at Alkhairaat University, Palu. The value of R-square 0.784 indicates that 78.4% leadership effectivity is affected by job motivation, physical and non-physical work environment, meanwhile 21.6% is affected by other variables that are not investigated in this research.